Recent Developments in Nitrone Chemistry: Some Novel Transformations - Yang, Jiong (Synlett, 2012)
Despite the long history of nitrone chemistry, novel transformations of nitrones continue to be discovered. This article describes some recent breakthroughs in the development of new transformations of nitrones. These new reactions include formal [3+3] cycloaddition of nitrones and vinylcarbenes to give 3,6-dihydro-1,2-oxazines, tandem cyclization–[3+3] cycloaddition of nitrones and enynones to give furo[3,4-d][1,2]oxazines, [2+2+3] cycloaddition of nitrones and 1,6-enynes to give tricyclic 1,2-oxazepanes, reaction of nitrones and 2-azido acrylates to form 1,2,4,5-tetrasubstituted imidazoles, and reactions of α,β-unsaturated N-aryl ketonitrones and activated alkynes to generate C3-quaternary indolenines.
Keywords: nitrone; dipolar cycloaddition; tandem reaction; catalysis; indolenine